Álgebras de Rees de ideais perfeitos de altura dois em três variáveis - Melo, Daynara Guimarães (2019)
In this dissertation we study the “Blowing-up” algebras of perfect ideals of codimension 2 in three variables. We pretend to discuss the algebras properties such as definition equations, Cohen-Macaulity and normality. The type of ideal that we approached in this paper was considered by [10] e [20].